Desarrollo e implementación de un sistema web para la gestión del programa de atención al adulto mayor "San Ignacio" del GAD Huaquillas. - Castillo Cañarte, Claudia Katherine (2014)
The program of care for the elderly "SAN IGNACIO" sponsored by GAD HUAQUILLAS which aims to provide comprehensive care and improve the quality of life of seniors, did not have the automation of processes, why it has developed and implemented a web system for management and control of technical and medical information for the benefit of older people, municipality and community, in addition to providing important data for evaluating organizations as the MIES.